Third World Studies Center 20th Anniversary Gathering - Garcia, Ed (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Excerpt from the TWSC Forum Just a few weeks ago, some of us met at the 10 th Anniversary Gathering of the Coalition for Peace at the Ateneo de Manila University campus. Today, some of us are once again meeting to commemorate not 10 but 20 years of the Third World Studies Center. (Ang tagal na pala!) It is almost frightening to think how often we meet nowadays to look back and commemorate, to remember past initiatives. However (and perhaps, this is a function of the passing years and - the wisdom one supposedly acquires in that passage). These occasions also provide us with an opportunity to reflect on their relevance and how to refashion them into the instruments or institutions they were truly meant to serve.